2015
DOI: 10.1097/meg.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal serum iron markers in chronic hepatitis B virus infection may be because of liver injury

Abstract: ObjectiveIn patients with chronic hepatitis B virus (HBV) infection, it is not known whether altered serum iron markers are directly because of the infection or the associated liver injury. We determined the serum iron status of patients with chronic HBV infection, and investigated whether it is HBV infection or HBV-related liver injury that likely causes abnormal serum iron markers in chronic HBV infection.Materials and methodsFor a retrospective study, chronic HBV-infected patients (80 patients with cirrhosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 23 publications
1
25
0
3
Order By: Relevance
“…To support this finding, a strong association between serum ferritin and HCC in patients with chronic liver disease was observed . In addition, serum iron and ferritin levels were found to be higher in HBV‐infected patients with cirrhosis compared with HBV‐infected patients without cirrhosis, suggesting that ferritin may play an important role in angiogenesis …”
Section: Role Of Iron In Oncogenesis By Virusesmentioning
confidence: 87%
“…To support this finding, a strong association between serum ferritin and HCC in patients with chronic liver disease was observed . In addition, serum iron and ferritin levels were found to be higher in HBV‐infected patients with cirrhosis compared with HBV‐infected patients without cirrhosis, suggesting that ferritin may play an important role in angiogenesis …”
Section: Role Of Iron In Oncogenesis By Virusesmentioning
confidence: 87%
“…Hepatitis B virus-infected patients with cirrhosis had low serum iron binding capacity and high ferritin in comparison with non-cirrhotic hepatitis B virus and hepatitis C infected patients. 18 Prieto J et al observed that higher ferritin was common in all patients with chronic liver disease. But most of the studies contradicted it.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that as hepatic parenchymal failure progresses, serum total iron binding capacity (i.e. TF activity) decreases (166,(171)(172)(173)(174)(175) and consequently TS increases. Increased TS was found to be a good predictor of the status of hepatic iron deposits (and fibrosis) in CHC (34,71,176,177).…”
Section: Hypotransferrinemia As a Cause Of Hepatic Siderosis In Cldsmentioning
confidence: 99%